CORPORATE SOCIAL RESPONSIBILITY SEBAGAI PEMODERASI PENGARUH KEPEMILIKAN MANAJERIAL DAN KEPEMILIKAN INSTITUSIONAL PADA KINERJA PERUSAHAAN - karmila, kadek karmilayani; Damayanthi, I Gusti Ayu Eka (E-Jurnal Akuntansi; Vol 14 No 3 (2016), 2016)
The company's performance illustrates the company's financial condition as reflected by performance in a period that was analyzed by financial ratios. Measurement of company performance is done to see whether the results of the company are in accordance with the planning. The purpose of this study was to determine the effect of managerial ownership and institutional ownership in the company's performance with corporate social responsibility as a moderating. This study was performed on companies listed in the Indonesia Stock Exchange in 2012-2014. The number of samples obtained as many as 132 companies, with a purposive sampling method. Independent variables used in this study is the managerial ownership and institutional ownership. The dependent variable used is the company's performance. The analysis technique used is moderated regression analisys (MRA). The results showed managerial ownership negative effect on the company's performance, institutional ownership has no effect on the company's performance, and CSR can not moderate the effect of managerial ownership and institutional ownership on company performance.
Keywords: Corporate Social Responsibility, Managerial Ownership, Institutional Ownership, Corporate Performance